2022-RA-1124-ESGO Predictors of invasive carcinoma in endometrial hyperplasia and its influence on surgical management. (20th October 2022) - Méndez, Carmen De la Fuente; Alonso-Espías, María; García-Pineda, Virginia; Gracia, Myriam; Siegrist, Jaime; Diestro, María Dolores; Hernández, Alicia; Zapardiel, Ignacio
Abstract : Introduction/Background: Endometrial hyperplasia consists of the proliferation of endometrial glands due to chronic exposure to high estrogen levels without the compensatory stimulus of progesterone. Other related factors are age, menopause and obesity. Transformation to endometrial cancer is greater if the hyperplasia is atypical; however, no reliable predictors have yet been described. The aim of this study is to analyze factors that can predict the evolution of hyperplasia to endometrial carcinoma. Methodology: A retrospective study was performed on patients diagnosed with endometrial hyperplasia at Hospital La Paz from January 2016 to December 2021. Factors that could influence the development of endometrial cancer were analyzed, as well as those that could influence oncologic outcomes. Results: 169 patients with endometrial hyperplasia were included, of which 41 progressed to carcinoma. In this group 92.7% of the carcinomas were endometrioid, 82.9% were diagnosed at FIGO stage IA, 68.3% were G1; statistical significance was observed in these associations. 3.6% of patients suffered recurrences, in which endometrioid carcinoma, stages IA, IB and IV, G2 and G3 and combined treatment showed significant association with this event. Of the disease-free patients, 96.8% had endometrioid carcinoma and 87.1% had stage IA. No significant differences were detected in survival studies. Conclusion: Advanced age, menopause, atypical hyperplasia, family history of cancer (specifically breast, colon and endometrial) and surgical treatment are statistically significantly associated with greater progression to endometrial cancer.